The DAMPAK WISATA DANAU BUATAN TERHADAP MASYARAKAT LOKAL DI SEKITAR SUMMARECON BEKASI: Pendahuluan, Rumusan Masalah, Tinjauan Pustaka, Metode Penelitian, Hasil dan Pembahasan, Daftar Pustaka - Surya Sanjaya (International Journal of Entrepreneurship and Tourism, 2024)
This research discusses the impact of artificial tourism on local communities with a focus on Lake Summarecon Bekasi. The research method used is descriptive qualitative involving business actors, managers and local communities as research subjects. Data was collected through observation, interviews and documentation. The research results show that the adoption of large businesses around lakes has significant economic and social impacts, but also shows the need for a balanced approach in developing businesses around lakes. The social and environmental impacts of tourists, such as changes in lifestyle, clothing, and language of local communities, as well as environmental impacts including flood control and environmental conservation, are also the focus of this research. Therefore, this research provides an in-depth understanding of the impact of artificial tourism on local communities and the environment